Transformasi Sosial dan Budaya Melalui Islamisasi di Sumatera Utara - Purnamasari, Ika; Zai, Diraningsih; SM, Indah Chofifah; Sembiring, Santa Hoky; Harifin (Islam & Contemporary Issues, 2024)
This research examines the social and cultural transformation that occurred in North Sumatra through the process of Islamization. The process of Islamization in this region has been underway since the 13th century, starting with the arrival of traders and scholars from the Middle East and Southeast Asia. This study uses a historical and sociological approach to analyze changes in the social structure, cultural practices, and value systems of North Sumatra society due to the acceptance and spread of Islam. The research results show that Islamization not only changes the religious aspects of society, but also influences patterns of social interaction, government systems, education, and local arts and culture. Significant changes include the establishment of Islamic educational institutions, the application of sharia law in several aspects of life, and the alignment of local traditions with Islamic teachings. This study also highlights the role of religious figures and Islamic institutions in directing this transformation. Thus, the process of Islamization in North Sumatra can be understood as a multifaceted phenomenon involving dynamic interactions between local traditions and Islamic values, resulting in a unique and diverse social and cultural identity. This research provides an important contribution to a deeper understanding of the dynamics of social and cultural change in the context of Islamization in Indonesia.